2022
DOI: 10.37934/araset.28.1.106115
|View full text |Cite
|
Sign up to set email alerts
|

Application of UAV and CSPI Matrix for Roof Inspection at Dewan Sultan Ibrahim and Dewan Tunku Mahkota Ismail UTHM

Abstract: Roof inspections are simply inspections to determine the roof integrity, durability, and long life of roofs before they need to be replaced. Besides, the hazards presented by these features bring problems to roof inspectors as they face difficulty in performing rooftop inspection due to its high roof structure. The purpose of this study is to access defective buildings with visual inspection with the help of Unmanned Aerial Vehicle (UAV), to classify roof building conditions using the CSP1 Matrix as a method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The simplest inspection is a visual inspection. Hamid et al, [2] examined the roof of the building using the Unmanned Aerial Vehicle (UAV). With this drone, some roof defects can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest inspection is a visual inspection. Hamid et al, [2] examined the roof of the building using the Unmanned Aerial Vehicle (UAV). With this drone, some roof defects can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…A group of agents in this study is associated with a UAV team and the task is associated with the agricultural tasks that need to be completed. However, different from Lu et al, [10], the capabilities of the agents are modified based on the possible UAV capabilities in solving some real agricultural-related tasks [14][15][16][17]. To improve the performance of the algorithm in Lu et al, [10] for solving task allocation problem in agriculture, the efficiency factor is also modified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the demand of technologies and approach for research is now relatively high as the technologies tend to develop rapidly. As an example, Kaamin et al, [6], demonstrated the utilization of UAVs for roof inspection, and the research conducted by Zaman et al, [7], employed UAVs and YOLOv5 for human detection in search and rescue operations, exemplify the increasing adoption of innovative solutions and technologies in various fields, highlighting the continuous development and integration of UAVs for diverse applications. Another study by Mokhtar et al, [8] and Siddiq et al, [9] demonstrate the ongoing research efforts in utilizing UAV photogrammetry to assess and understand coastal erosion phenomena.…”
Section: Introductionmentioning
confidence: 99%